EFFECTIVENESS OF MIND MAPPING TO INCREASE STUDENT’S SCIENTIFICT LITERACY - Andi Kurniawan; Sofan Rizki; Suharto; Sayyida Khairotun Nisak; Tomi Apra Santosa (Adisam Publisher, 2023)
This study aims to determine the effectiveness of the mind maps model to improve students' science literacy. This type of research is a meta-analysis study. This study analyzed 14 effect sizes obtained from google scholar, DOAJ, ScienceDirect and ERIC databases. The inclusion criteria are publications published in 2019-2023, research comes from journals or proceedings indexed by SINTA, Scopus and WOS, Research has experimental classes with mind mapping models and conventional model control classes, research must be in Indonesian and English and data has sample size, standard deviation and mean value. Data analysis with the help of JASP applications. The results of the study concluded From the studyit can be concluded that the results of the study concluded the value of summary effect size or mean effect size of rE = 0.937; Z = 6.768; p < 0.001. This finding explains that the mind mapping model is effective in increasing students' science literacy in learning with high categories.